2012
DOI: 10.1002/etc.1968
|View full text |Cite
|
Sign up to set email alerts
|

Chlorophacinone residues in mammalian prey at a black‐tailed prairie dog colony

Abstract: Black-tailed prairie dogs (BTPDs), Cynomys ludovicianus, are an important prey for raptors; therefore, the use of the rodenticide Rozol (0.005% chlorophacinone active ingredient) to control BTPDs raises concern for secondary poisonings resulting from the consumption of contaminated prey by raptors. In the present study, the authors observed Rozol exposure and adverse effects to mammalian prey on 11 of 12 search days of the study. Mammalian hepatic chlorophacinone residues ranged from 0.44 to 7.56 µg/g. Poisone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 14 publications
2
2
0
Order By: Relevance
“…The levels of chlorophacinone residues in the livers of black‐tailed prairie dogs (0.06–8.4 mg kg −1 ) were similar to those reported for prairie dogs in another study (0.44–7.56 mg kg −1 ) . Compared with other species, the maximum residues from prairie dogs were between the maximum reported for laboratory rats (24.9 mg kg −1 ) in a lab study and those reported for Belding's ground squirrel ( Urocitellus beldingi ; 0.82 mg kg −1 ) and Microtus spp.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The levels of chlorophacinone residues in the livers of black‐tailed prairie dogs (0.06–8.4 mg kg −1 ) were similar to those reported for prairie dogs in another study (0.44–7.56 mg kg −1 ) . Compared with other species, the maximum residues from prairie dogs were between the maximum reported for laboratory rats (24.9 mg kg −1 ) in a lab study and those reported for Belding's ground squirrel ( Urocitellus beldingi ; 0.82 mg kg −1 ) and Microtus spp.…”
Section: Discussionsupporting
confidence: 79%
“…The residues were highest during 3–6 days post‐exposure, but declined sharply in subsequent days. A field study using Rozol bait found a similar sharp decline in residues in the livers of dead prairie dogs; however, residue analyses were not conducted until carcasses were first observed above ground ≥12 days post‐exposure . The residue levels on day 12 of this field study (x ∼ 3.4 mg kg −1 ) closely matched the levels we detected on day 5 (x = 3.4 mg kg −1 ) post‐exposure.…”
Section: Discussionsupporting
confidence: 71%
“…Using hematocrit and blood clotting times as endpoints, dietary exposure of captive kestrels to environmentally realistic concentrations (Merson et al 1984, Primus et al 2001, Ramey et al 2007, Vyas et al 2012, Pitt et al 2015, Shore and Coeurdassier 2018 of the FGAR chlorophacinone or the SGAR brodifacoum did not affect sensitivity to a subsequent low-level dietary dose of chlorophacinone. Based upon previous studies in kestrels (Rattner et al 2015), a seven-day, no-choice dietary exposure to 1.5 µg chlorophacinone/g-ww or to 0.5 µg brodifacoum/g ww evokes coagulopathy and results in substantial hepatic residues of these ARs.…”
Section: Discussionmentioning
confidence: 99%
“…A complicating factor is that some of the reported AR residue values (Primus et al ; Ramey et al ; Pitt et al ) were derived from carcass samples from which liver had been removed. This may underestimate exposure because brodifacoum and chlorophacinone concentrations in liver of small mammal prey can be much greater than in the rest of the body (e.g., Vyas et al ; Shore and Coeurdassier ). Moreover, hawk species for which the kestrel may be the most appropriate model do not ingest entire mammalian prey but feed selectively on liver, brain, muscle, and some organs.…”
Section: Methodsmentioning
confidence: 99%